Knowledge and Virtue in Plato’s Meno - Ferrari, Franco (Revista Archai, 2025)
The theme of the nature of virtue and its transmissibility runs through almost all the early dialogues of Plato, that is, the so-called “Socratic dialogues.” It acquires a central importance in the Protagoras and Meno, which opens with the question about the way to acquire virtue. During the dialogue, virtue assumes a highly political significance: Meno asks Socrates how we can achieve success in the political field, as we might acquire social recogni-tion. The thesis around which the conversation develops assumes the identity of virtue and knowledge (episteme). However, the consequence which follows from the assump-tion of this thesis, that is, the principle according to which virtue, because knowledge, is teachable is refuted by the famous “empirical argument”: the absence of men able to transmit the their virtues to their children shows that it is not teachable, and therefore not knowledge. Socrates then proposes to locate the source of political virtue in correct opinion (orthe doxa). However, the empirical validity of the argument is highly uncertain, since it seems to be based on the ambiguity of the meaning of the term didakton, which means both “teachable” and actually “taught”. Even the attempt to establish virtue on theia moira should be treated with some skepticism. In fact, Socrates alludes at the end of the dialogue, to the possibility that there is a man who is virtuous and who is also able to teach virtue to another man: this extraordinary man is naturally Socrates himself.